Historicising the question of socialisation into “popular music” - Marc Perrenoud (Transposition)
This article is more of a programmatic text than a specific research report. It aims to show the necessity of a historicization of the question of musical socializations, in particular in the field of popular music which appeared during the 20th century and evolved much in a few decades. Based on a set of sociohistorical works, including those conducted by the author for the last twenty-five years (field surveys in France and Switzerland mainly), the article highlights the drastic evolution of the conditions of possibility of a coming to musical practice in the last sixty years.